Geoconservação e proposta de uso sustentável do patrimônio paleontológico do Norte do Estado do Tocantins e Sudoeste do Estado do Maranhão - Lopes, Raylon da Frota (2024)
In the central-northern region of Brazil, in the northern state of Tocantins and the southwestern state of Maranhão, there are known fossiliferous outcrops with notable scientific importance. These occurrences date from the Permian to the Cretaceous of the Intracratonic Sedimentary Basin of Parnaíba and require geoconservation strategies for their proper sustainable use and management. Although scientific knowledge has already been produced about the paleontological heritage present in the study area, until now no research had been conducted with a geoconservation approach including inventory, quantification of values and potentials for use, and vulnerability for the geosites in this region.The general objective of this work is to characterize the paleontological heritage originating from the Paleozoic and Mesozoic of the northern region of Tocantins and southwestern Maranhão in its physical aspects and social relevance. To achieve the proposed objective, a bibliographic survey and fieldwork were carried out to prepare the inventory of the fossiliferous outcrops in the studied area. In the quantification of the values and potentials for use of the outcrops, the Geossit platform, developed by the Geological Survey of Brazil, was used. The inventoried fossils consist of shark somatofossils, gymnosperm trunks, and mineralized ferns, sauropod and theropod ichnofossils, and indeterminate leaf molds. For the quantitative assessment, only geosites were considered, namely: the geosites comprising the Natural Monument of Fossilized Trees of Tocantins in Filadélfia (Permian); the geosite containing theropod dinosaur footprints in Fortaleza dos Nogueiras, Maranhão (Triassic); and the geosite containing sauropod dinosaur footprints in Itaguatins, Tocantins (Early Cretaceous). Overall, the geosites obtained scientific value and potentials for educational and tourist use ranging from moderate to high, and a low risk of degradation for the outcrops of the Natural Monument of Fossilized Trees of Tocantins, medium for the theropod footprints, and high for the sauropod footprints.The studied locations have the potential for geoeducational and geotouristic activities, which can contribute to the social and economic development of the region. However, each geosite must be utilized considering specific strategies that respect their potentials and limitations.